2014
DOI: 10.1039/c3tb21832e
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of protected oligourethanes as crosslinkers of collagen-based scaffolds

Abstract: This paper describes the preparation and characterization of water-soluble urethane oligomers bearing protected isocyanate groups. It also points out its ability to crosslink decellularized pericardium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 45 publications
(79 reference statements)
1
40
0
1
Order By: Relevance
“…It has been reported that chemically cross-linked collagen using EDC facilitates higher rates of human fibroblasts migration and new tissue formation than physical cross-linking based on dehydrothermal treatment or ultraviolet light [26]. A multitude of different material compositions, comprising a collagen component with increased stability against degradation and thus diverse application areas like bone tissue engineering [27], soft tissue engineering [28] and also decellularized scaffolds [29] were treated with HMDI for chemical cross-linking to increase their stability. Therefore, HMDI was also included as a cross-linker in the present study.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that chemically cross-linked collagen using EDC facilitates higher rates of human fibroblasts migration and new tissue formation than physical cross-linking based on dehydrothermal treatment or ultraviolet light [26]. A multitude of different material compositions, comprising a collagen component with increased stability against degradation and thus diverse application areas like bone tissue engineering [27], soft tissue engineering [28] and also decellularized scaffolds [29] were treated with HMDI for chemical cross-linking to increase their stability. Therefore, HMDI was also included as a cross-linker in the present study.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, breaking tensile stress can be notably enhanced by grafted poly(IPA) without a decrease in breaking tensile strain. Breaking tensile stress and strain values of the IPA series highly surpass those of the reported PUs [44][45][46] and demonstrate the structural supremacy of lightly crosslinked PU obtained from the grafting steps. Percent shape recovery at 10 C rapidly increases compared with that of L as the IPA monomer content increases and remains above 95% at high IPA monomer content (Table 3).…”
Section: Tensile and Shape Memory Propertiesmentioning
confidence: 83%
“…The most common methods produce excessive crosslinking in the implants of collagen which, although avoids rapid implant reabsorption by the host in the medium term, decreases its biocompatibility exacerbating a foreign body reaction. We presented the alternative management of GO with a pericardial implant with enhanced mechanical and biodegradation resistance by its crosslinking with oligourethane molecules . The use of the oligourethane as crosslinker is an alternative to the traditional crosslinking methods, because it produces a slight crosslinking, consequently, a lower chronic inflammatory process .…”
Section: Discussionmentioning
confidence: 99%
“…a). Previously, the implant was manufactured from bovine pericardium applying methods of decellularization and crosslinking with oligourethane , as well as freeze‐drying and gamma irradiation to sterilize it. The surgical procedure was carried out with the informed consent from the patient's parents.…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation